Bioremediating Oil Spills in Nutrient Poor Ocean Waters Using Fertilized Clay Mineral Flakes: Some Experimental Constraints. (23rd June 2013) - Warr, Laurence N.; Friese, André; Schwarz, Florian; Schauer, Frieder; Portier, Ralph J.; Basirico, Laura M.; Olson, Gregory M.
Abstract : Much oil spill research has focused on fertilizing hydrocarbon oxidising bacteria, but a primary limitation is the rapid dilution of additives in open waters. A new technique is presented for bioremediation by adding nutrient amendments to the oil spill using thin filmed minerals comprised largely of Fullers Earth clay. Together with adsorbed N and P fertilizers, filming additives, and organoclay, clay flakes can be engineered to float on seawater, attach to the oil, and slowly release contained nutrients. Our laboratory experiments of microbial activity on weathered source oil from the Deepwater Horizon spill in the Gulf of Mexico show fertilized clay treatment significantly enhanced bacterial respiration and consumption of alkanes compared to untreated oil-in-water conditions and reacted faster than straight fertilization. Whereas a major portion (up to 98%) of the alkane content was removed during the 1 month period of experimentation by fertilized clay flake interaction; the reduced concentration of polyaromatic hydrocarbons was not significantly different from the non-clay bearing samples. Such clay flake treatment could offer a way to more effectively apply the fertilizer to the spill in open nutrient poor waters and thus significantly reduce the extent and duration of marine oil spills, but this method is not expected to impact hydrocarbon toxicity.